Effect of passive immunization with mouse Anti-BCG 64 kDa protein on ehrlich ascites carcinoma cells - Chowdhury, Maisha Mosharrat (BRAC University, 2018)
This thesis report is submitted in partial fulfilment of the requirement for the degree of M.Sc in Biotechnology, 2012.